Impact of Employee Performance Monitoring on Knowledge Workers' Productivity: The Serial Mediation Effects of Stress and Knowledge Management in the UAE Construction Industry - Muneer, Aldwaikat (Universiti Malaysia Sarawak, 2022)
This study aims to present and test a new conceptual framework to study the significance of employee performance monitoring for knowledge worker productivity in the UAE construction industry. Previous research tends to overlook the mediation effects of stress and knowledge management. In this study, data is collected from 595 executives and non-executives having a minimum of three years of service tenure and a diploma or higher educational qualification from all the seven emirates of the UAE. Because of multivariate analysis, structural equation modeling is used in the two stages of measurement model accuracy and structural relationships among study constructs. This study demonstrates the direct effect of employee performance monitoring on knowledge worker productivity and the statistically significant mediating impact of stress and knowledge management in the relationship between employee performance monitoring and knowledge-worker productivity. Although stress's direct effect on knowledge has a negative beta coefficient, it is still statistically insignificant. Such statistical insignificance reflects that stress does not affect knowledge worker productivity significantly. This study has made a significant theoretical contribution to the larger body of knowledge by establishing the impact of employee performance monitoring on knowledge worker productivity, proving the mediating role of stress in between employee performance monitoring and knowledge management, and proving the mediating effect of stress in the relationship of employee performance monitoring and knowledge worker productivity. Furthermore, this study has other theoretical, empirical, methodological, and practical contributions. This study's results will contribute to policymakers, analysts, and project managers.